Analysis of the Occupational Health and Safety Effects on Productivity of Employees using Partial Least Squares Methods - Ukhisia, Bella Gloria; Astuti, Retno; Hidayat, Arief (Fakultas Teknologi Pertanian Universitas Brawijaya, 2013)
Occupational safety and health is one of the important factors that can affect employees’ productivity. Risk of accidents and occupational diseases often occur because the occupational safety and health program is not performing properly which can have an impact on the level of employees’ productivity. The aims of the research were to determine the effect of occupational safety variable and occupational health variable on employees’ productivity, and occupational safety on occupational health at installation division of PG Krebet Baru II Malang. The study was conducted at the installation division of the PG Krebet Baru II Malang using sample size of 60 people. Variables used in this study consisted of two types, i.e. latent variables and indicator variables. Data were collected using a questionnaire which was consisted of questions include all research variables and the response was measured using a Likert scale. The data then were analyzed by partial least squares method using software SmartPLS ver 2 for windows. The results showed that the occupational safety variable with regression coefficient 0.137 did not give a significant impact on employees’ productivity. Occupational health variable with regression coefficient 0.258 gave a significant impact on employees’ productivity. Safety variable with regression coefficient 0.587 gave a significant impact on occupational health. It can be concluded that occupational safety did not give a directly significant effect on employees’ productivity, occupational safety indirectly affect employees’ productivity through occupational health, occupational health directly gave a significant impact on productivity of employees.Keywords: Occupational health and safety, Partial Least Squares, Productivity